Valorization Strategies for a By-Product of Organic Tomato Processing as Potential Ingredient in Functional Food Formulations - López Bermúdez, Yhonattan Nicolás; Aldana Heredia, Juan Felipe; Sánchez-Camargo, Andrea del Pilar; Hernández-Carrión, María (Frontiers in Food Science and Technology, 2022)
Production of tomato-based products generates a percentage of waste of 5%, composed mainly of peel. This has a significant source of carotenoids, such as lycopene, and an appropriate amount of total dietary fiber (TDF). Both carotenes and dietary fiber are known to have functional effects on the human body. Therefore, the aim of this research work was mainly divided into two parts. Firstly, the characterization of organic tomato peel obtained by a local processing industry in terms of percentage of macronutrients as dietary fiber, protein, and ash, as well as total carotenoid content, was done. Secondly, two valorization alternatives of these compounds as potential functional additives in food processing were proposed. The first one included a carotenoid extraction using UAE and the encapsulation of the enriched-carotenoids extract using spray-drying technology and its subsequent analysis of powder properties. The second one evaluated the potential use of TDF tomato peel as a replacement of fat and flour in the four formulations of cookies. Each formulation was assessed using physicochemical, texture, sensory, and theoretical proximal analyses. For the results, UAE optimization was performed using a solvent ratio of 80:20 Ethyl Acetate:Ethanol and 2.5% w/v of biomass – solvent ratio. A recovery percentage of total carotenoid content of 89.08% was obtained. The content of TDF was 49.46 (3.91) g/100g on a dry basis. For encapsulation, the drying yield and encapsulation efficiencies were 67.3% (0.5) and 58.1% (0.8), respectively. Sensory analysis showed no significant difference between the means for the control cookie and 30% fat replacement cookie. Thus, these cookies were the most purchase intention by the consumers. Consequently, this study presented a solution towards unused tomato peel industrial by-product promoting the design of new functional food products with high content of carotenes and dietary fiber, increasing nutritional and health benefits to consumers.